Isolation and Characterization of Mesenchymal Stem Cells from Human Skin - Aralbek, A.B.; Ogay , V.B. (Eurasian Journal of Applied Biotechnology, 2025)
Mesenchymal stem cells (MSCs) derived from human skin dermis are of considerable interest in regenerative medicine due to their high proliferative activity, self-renewal capacity, and multilineage differentiation potential. In this study, a primary culture of dermal MSCs was obtained and characterized through enzymatic digestion of skin biopsies using dispase and collagenase, followed by cultivation in various nutrient media. Morphological assessment, karyotyping, and immunophenotypic analysis confirmed that the cells belonged to the MSC population (CD105⁺, CD90⁺, CD45⁻). Comparative experiments were conducted to identify the optimal culture medium and seeding density. It was established that DMEM/F12 + 10% FBS medium yielded the highest increase in cell mass, while a seeding density of 3.5×10³ cells/cm² supported effective proliferative expansion. Moreover, the dermal MSCs demonstrated the ability to differentiate into osteoblasts, chondrocytes, and adipocytes. The results obtained highlight the high biological activity of human skin MSCs and their promising potential for applications in cell therapy and tissue engineering.